Level of Service (LOS) and bus headways : a case study of George Town, Penang - Siti Fadhlina Muhammad Fisal,; Nur Sabahiah Abdul Sukor, (Penerbit Universiti Kebangsaan Malaysia, 2021)
Bus ridership is affected by the quality of the bus service. Level of Service (LOS) and bus headways are among the key factors for the quality of bus service. This study aims to measure the quality of bus service based on Level of Service (LOS), the reliability of bus headway and its relationship with the number of private vehicles in George Town CBD of Penang. Several bus route for Rapid Penang bus services (11, 101, 201, 301, CAT and CT7) were selected according to the maximum headway (30 minutes) that calculated using the Transit Capacity and Quality Service Manual (TCQSM). Bus arrival time was observed at the bus stops and the traffic count was conducted to obtain the volume of private vehicles during peak hours. Level of Service (LOS) was determined using TCQSM on-time performance calculations. This study found that bus route No 11, 101, 201 and 301 did not comply with the estimated headway schedule. These bus routes were classified as LOS D and LOS E, whereas bus route CAT showed reliable service with LOS A and LOS B. Interestingly, the findings also reported that the high number of private vehicles affecting only LOS and the reliability of certain bus routes were significant. It shows that there are other limiting factors that cause the bus services unreliable and thus increase the waiting time of passengers.